Late Triassic Metatonalite from the Schwaner Mountains in West Kalimantan and Its Contribution to Sedimentary Provenance in the Sundaland - Nugroho Imam Setiawan; Yasuhito Osanai; Nobuhiko Nakano; Tatsuro Adachi; Lucas Donny Setiadji; Joko Wahyudiono (Ikatan Ahli Geologi Indonesia, 2013)
This contribution presents petrography, geochemical characteristicc and LA-ICP-MS U-Pb zircon dating from metatonalites in the Schwaner Mountains of West Kalimantan. The metatonalites mainly consist of plagioclase, biotite, quartz, apatite, muscovite, and titanite with relict clinopyroxene surrounded by hornblende. The geochemical characteristics show that the rocks have calc-alkaline affinities and were derived from subduction-related arc tectonic environment. Some of the metatonalites have adakite signature, which suggests the Schwaner Mountains were not formed by a consecutive subduction system. The result of LA-ICP-MS U-Pb zircon dating reveals that the metatonalite has magmatic age at 233 ± 3 Ma (Late Triassic), which is the oldest magmatic age in the Schwaner Mountains. Therefore, it strongly suggests that the Schwaner Mountains has significantly potential for important sedimentary sources in Sundaland not only from Cretaceous age but also from Triassic age as well as Tin Belt granites from Malay Peninsula.